Evaluation of a training program for medicines-oriented policymakers to use a database of systematic reviews - Colquhoun, Heather L; Lowe, Dianne; Helis, Eftyhia; Belanger, Denis; Ens, Brendalynn; Hill, Sophie; Mayhew, Alain; Taylor, Michael; Grimshaw, Jeremy M (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background Suboptimal prescribing and medications use is a problem for health systems globally. Systematic reviews are a comprehensive resource that can help guide evidence-informed decision-making and implementation of interventions addressing such issues; however, a barrier to the use of systematic reviews is their inaccessibility (due to both dispersion across journals and inaccessibility of content). Publicly available databases, such as Rx for Change, provide quick access to summaries of appraised systematic reviews of professional and consumer-oriented interventions to improve prescribing behaviour and appropriate medication use, and may help maximise the use of evidence to inform decisions. The present study aims to evaluate a training program to improve attitudes towards, confidence in skills, intentions to use, and use of systematic review evidence contained within Rx for Change. Methods Guided by the Knowledge to Action framework, a training program with content customised to local provider and consumer contexts was developed with knowledge user input. The training program consisted of a 6 minute information video, a 1 hour workshop with hands-on, interactive and didactic components, and two post-training reminders. Forty-nine people from five medicines-focused organisations in Canada and Australia attended one of six workshops. Participants were surveyed immediately pre and post and 3 months after training to evaluate their attitudes towards, confidence in skills, intentions to use, and use of Rx for Change, and attitudes towards and confidence in skills for using evidence for decision-making. Analyses for differences for each of the outcomes at three time points (pre, post and 3 months after training) was performed using a random effects model. Results Immediately post-training, there were higher respondent attitudes towards Rx for Change (mean increase = 0.54 out of 5, 95% CI, 0.18–0.83, P < 0.005); intention to use Rx for Change (0.53, 95% CI, 0.21–0.86, P < 0.005); confidence in skills for using Rx for Change (2.08, 95% CI, 1.74–2.42, P < 0.005); and confidence in skills for using evidence in policy decision-making (0.50, 95% CI, 0.22–0.77, P < .005) compared to pre-training. Confidence in skills for using both Rx for Change and evidence were maintained 3 months after training (both P < 0.005). Conclusions Participants of this training program reported sustained improvements in their confidence in skills for using evidence in policy decision-making. This may have important implications for uptake of systematic review evidence promoting improved prescribing and medication use.